RAP44 phage integrase-guided 50K genomic island integration in Riemerella anatipestifer - Wang, Ying; Deng, Jianfeng; Ren, Jianle; Liang, Libin; Li, Junping; Niu, Sheng; Wu, Xingchen; Zhao, Yujun; Gao, Shimin; Yan, Fang; Liu, Yuqing; Ma, Haili; et al. (Frontiers in Veterinary Science, 2022)
Bacteriophages are viruses that infect bacteria. Bacteria and bacteriophages have been fighting for survival. Over time, the evolution of both populations has been affected. Pathogenic Flavobacteriaceae species including Riemerella anatipestifer mainly infects ducklings, geese, and turkeys. However, it does not infect humans, rats, or other mammals, and is a suitable and safe research object in the laboratory. Our previous study showed that there is a 10K genomic island in R. anatipestiferIn this study, we found another integrated 50K genomic islands and focused on the relationship between R. anatipestifer genomic islands and the RAP44 phage genome. The phage RAP44 genome was integrated into R. anatipestifer chromosome, and an evolutionary relationship was evident between them in our comparative analysis. Furthermore, the integrated defective RAP44 phage sequence had the function of integration, excision, and cyclization automatically. Integrases are important integration elements. The integrative function of integrase was verified in R. anatipestifer. The integrase with the attP site can be integrated stably at the attB locus of the R. anatipestifer genome. A recombinant strain can stably inherit and express the exogenous gene. By studying the integration between host bacterium and phage, we have provided evidence for the evolution of the genomes in R. anatipestifer.